2022
DOI: 10.1111/mpp.13230
|View full text |Cite
|
Sign up to set email alerts
|

Dehydroascorbate induces plant resistance in rice against root‐knot nematode Meloidogyne graminicola

Abstract: Ascorbic acid (AsA) is an important antioxidant in plants and regulates various physiological processes. In this study, we show that exogenous treatments with the oxidized form of AsA, that is, dehydroascorbate (DHA), activates induced systemic resistance in rice against the root‐knot nematode Meloidogyne graminicola , and investigate the molecular and biochemical mechanisms underlying this phenotype. Detailed transcriptome analysis on roots of rice plants showed an early and robust tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 118 publications
(181 reference statements)
3
21
0
Order By: Relevance
“…Transcriptional analysis of roots of rice seedlings revealed a notable induction of the DP biosynthetic pathway 24 h after PA treatment, the same time point at which plants were inoculated with M. graminicola (Table 1). Interestingly, an in‐house transcriptome dataset of plants at 1 d post treatment with DHA showed a similar induction of root DP biosynthesis (Chavan et al ., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Transcriptional analysis of roots of rice seedlings revealed a notable induction of the DP biosynthetic pathway 24 h after PA treatment, the same time point at which plants were inoculated with M. graminicola (Table 1). Interestingly, an in‐house transcriptome dataset of plants at 1 d post treatment with DHA showed a similar induction of root DP biosynthesis (Chavan et al ., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…JaMYB and AOS2 are marker genes for JA-dependent signaling pathways, whereas ERF1 and ACS1 are markers of the ET signaling pathway ( Leonetti et al, 2017 ; Salman et al, 2022 ). Previous studies on rice have also shown that the exogenous application of plant hormones and antioxidants induces systemic defense against M. graminicola, and that the JA pathway plays a pivotal role in the induction of defense against RKN ( Nahar et al, 2011 ; Singh et al, 2020 ; Chavan et al, 2022 ). Conversely, abscisic acid (ABA), brassinosteroids (BRs), gibberellic acid, and strigolactones promote the susceptibility of rice to M. graminicola infection by interacting antagonistically with the JA pathway ( Nahar et al, 2012 ; Yimer et al, 2018 ; Lahari et al, 2019 ).…”
Section: Discussionmentioning
confidence: 98%
“…Roots from five seedlings were pooled to form one sample, and three pooled samples were created per treatment. Plants treated with BTH, BABA or PA, and their corresponding control plants, were grown by the author for this study; mRNA-seq on DHA-treated plants and their control plants was performed earlier (Chavan et al, 2022). The same growth chamber, light and temperature settings an batch of Kitaake seeds were used for both experiments.…”
Section: Mrna Sequencingmentioning
confidence: 99%
“…In agreement with previously published results (Nahar et al, 2011;Ji et al, 2015;Singh et al, 2020;Desmedt et al, 2021a), pre-treatment with 3.5 mM β-aminobutyric acid (BABA), 300 µM piperonylic acid (PA), 250 µM benzothiadiazole (BTH) or 20 mM dehydroascorbic acid (DHA) reduces rice susceptibility to the root-knot nematode M. graminicola (Figure 1a). As previously shown, two applications of PA are required to induce full resistance (Desmedt et al, 2021a(Desmedt et al, , 2022; for this reason, further experiments were performed on plants treated with PA twice. BABA, BTH and PA caused no phytotoxicity and had no effect onplant growth (Figure 1b-c).…”
Section: Four Chemically Distinct Ir Stimuli Induce Systemic Resistan...mentioning
confidence: 99%
See 1 more Smart Citation